2016
DOI: 10.1371/journal.pone.0157760
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pregnancy Intention and Professional Antenatal Care Utilization in Bangladesh: A Nationwide Population-Based Survey

Abstract: ObjectiveTo investigate the association between maternal pregnancy intention and professional antenatal and delivery care utilization.MethodsOur data were derived from the 2011 nationally representative Bangladesh Demographic Health Survey. We included antenatal and delivery care utilization data of the most recent live births for women for the previous three years (n = 4672). We used multilevel logistic regression models to assess the relationship between pregnancy intention and use of professional antenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
44
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 48 publications
17
44
2
2
Order By: Relevance
“…One possibility is that women with unintended pregnancies are likely to recognize their pregnancy in a later stage, which means they miss the opportunity to access comprehensive maternal health services during pregnancy [41]. Another explanation could be that women with an unintended pregnancy may be less pro-active about seeking out health care [14]. Notably, the association between unintended pregnancy and maternal complications holds true even after accounting for health service utilization (ANC and ASHA home visits) during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that women with unintended pregnancies are likely to recognize their pregnancy in a later stage, which means they miss the opportunity to access comprehensive maternal health services during pregnancy [41]. Another explanation could be that women with an unintended pregnancy may be less pro-active about seeking out health care [14]. Notably, the association between unintended pregnancy and maternal complications holds true even after accounting for health service utilization (ANC and ASHA home visits) during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened maternal risk in Uttar Pradesh can be attributed, at least in part, to poorer maternal health care utilization, including antenatal care (ANC) [9]. Studies from India and elsewhere indicate that women with an unintended pregnancy are less likely to recieve ANC [6,[10][11][12][13][14][15][16]. In India, ANC care has received expanded attention via home visits to pregnant women by community outreach workers known as Accredited Social Health Activists-ASHAs, with a focus on socially vulnerable women (e.g., poorer, less educated, adolescents); although vulnerable women are more likely to be approached via ASHAs relative to clinicians, not all women are reached [17].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the richest wealth quintile spent significantly more than poorest quintile, although higher cost does not always guarantee the better birth outcome . However, it was well reported that the wealthiest households always used more maternal care services than those in the poorest households, in the Bangladeshi context . Recent studies indicated that the utilization of C‐section was highly concentrated among mothers from the richest wealth quintiles, and even the poorest mother often had difficulties accessing this life‐saving procedure .…”
Section: Discussionmentioning
confidence: 99%
“…To date, some studies (e.g. Marston and Cleland 2003;Wado et al 2013;Rahman 2015;Rahman et al 2016;Baschieri et al 2017;Echaiz et al 2018) have analysed the effect of unintended pregnancies on health and healthcare utilization in LMICs. However, the findings from these studies have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%